POTENSI SUMBERDAYA EKONOMI DAERAH: SEBUAH TINJAUAN ASPEK EKONOMI BAGI USAHA MIKRO KECIL MENENGAH - I Ketut R. Sudiarditha (Fakultas Ekonomi Universitas Negeri Jakarta, 2010)
ABSTRACTPotency effort for micro, small and medium-size enterprises in Indonesia very potential to be developed in the effort absorbtion of labour and at the same time prosperity public. The many small business emerging in when crisis to give indication that Indonesia chartered investment counsel potency still need to be developed furthermore. Its the expansion is till now unable to be pushed by innovation factor and usage of information of technology. Effort for small and medium-size enterprises in Indonesia can be developed in: First, expansion of real soul and entrepreneurs character. Needs more entrepreneurses in Indonesia borne by pushed by vision and innovation. Second, skilled expansion enlarges business; small business activity which there are having to constructed and developed. Third, direction and excellence expansion competes nation. Interaction and the relation of the existing inter-states more influenced by chartered investment counsel factor. Therefore to can become pre-eminent nation and considered, hence Indonesia must soon finds and develops excellence of its the core.Keywords: Economic Resourses, Micro Small and Medium-size Enterprises.